2008
DOI: 10.1007/s00332-008-9029-7
|View full text |Cite
|
Sign up to set email alerts
|

Gevrey Regularity for the Attractor of the 3D Navier–Stokes–Voight Equations

Abstract: Recently, the Navier-Stokes-Voight (NSV) model of viscoelastic incompressible fluid has been proposed as a regularization of the 3D Navier-Stokes equations for the purpose of direct numerical simulations. In this work we prove that the global attractor of the 3D NSV equations, driven by an analytic forcing, consists of analytic functions. A consequence of this result is that the spectrum of the solutions of the 3D NSV system, lying on the global attractor, have exponentially decaying tail, despite the fact tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 28 publications
0
78
0
Order By: Relevance
“…The estimates of the fractal and Hausdorff dimensions of the global attractor were later improved in [33], where also an upper bound on the number of asymptotic determining modes of the solutions was provided. Concerning the regularity of the attractor, it can be proved to be as smooth as the forcing term f permits, and even real analytic, whenever f is analytic as well [32].…”
Section: Lemma 33mentioning
confidence: 99%
See 1 more Smart Citation
“…The estimates of the fractal and Hausdorff dimensions of the global attractor were later improved in [33], where also an upper bound on the number of asymptotic determining modes of the solutions was provided. Concerning the regularity of the attractor, it can be proved to be as smooth as the forcing term f permits, and even real analytic, whenever f is analytic as well [32].…”
Section: Lemma 33mentioning
confidence: 99%
“…Moreover, the robust analytical properties of the 3D NSV model ensure the computability of solutions and the stability of numerical schemes. Finally, there is evidence that the 3D NSV with a small regularization parameter enjoys similar statistical properties as the 3D NSE [32,44]. In this connection, understanding the long-time behavior of solutions to the 3D NSV equation is crucial.…”
Section: Introductionmentioning
confidence: 98%
“…On bounded domains, the NSV equations have been deeply studied. One can see Oskolkov [16], Kalantarov [10,11], Kalantarov et al [12], Kalantarov and Titi [13], García-Luengo et al [9], Gao and Sun [8], Qin et al [18], etc.…”
Section: Introductionmentioning
confidence: 97%
“…BV-Voigt is a regularization of the BV model based on the Navier-Stokes-Voigt (NSV) equations [5], an incompressible viscoelastic model which is a smooth regularization of Navier-Stokes equations [4]. In [5] it is showed that NSV reduces the stiffness of direct numerical simulations of turbulent flows, with small impact in the energy containing scales.…”
Section: Introductionmentioning
confidence: 99%